Treatment of Poorly Differentiated Neuroendocrine Carcinoma of the Pancreas - Gupta, Anumeha; Duque, Marvin; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Poorly differentiated neuroendocrine carcinoma is a rare malignancy that remains a challenge to treat. Poorly differentiated neuroendocrine carcinoma occurs at an incidence of 2% annually in United States. The current standard of care is based largely upon retrospective data. There remains a need for large prospective cooperative group trials in the management of poorly differentiated neuroendocrine carcinoma. In this paper, we will review abstract #e15096 (Paclitaxel, carboplatin, and etoposide (TCE) in advanced poorly differentiated neuroendocrine carcinoma) by Loeffler et al. and #e15071 (Poorly differentiated neuroendocrine carcinoma (NEC G3): prognostic factors and potential novel targets) by Heetfeld et al. presented at the 2013 ASCO Annual Meeting highlighting treatment options in first and second lines for poorly differentiated neuroendocrine carcinoma. Image: Main gate, Tufts University. Medford, MA, USA. (Author: Daderot; Wikimedia Commons)